Sentido e Causalidade: preâmbulos de uma teoria da história weberiana - VALLE, Ulisses do (2010)
The main purpose of this dissertation is to get a sistematization of the concept of meaning, disposed diffusely in Max Weber's work. The criterion around which spins this sistematization is its relevance to a theory of historical knowledge and, therefore, its relevance to scientific history. The concept of meaning implements a web of problems and also of possibilities to the realm of historical causation. The historical science has both its subject, the historian, as its object, the past, as dependents of the implications that the concept of meaning delimits to the causal consideration, methodologically oriented, of the historical events